The distribution of public green spaces in relation to the socioeconomic characteristics of the population in Ciudad Juárez, Mexico - Herrera Correa, Victor Manuel; Romo Aguilar, María de Lourdes (Acta Universitaria, 2022)
Public green spaces (PGS) offer multiple benefits to urban populations. Unequal access to these spaces for the different socioeconomic groups of the population would represent a spatial injustice. In this article, the PGS distribution in Ciudad Juárez, Mexico, is analyzed to determine the current relationship between their characteristics (location, number, size, and endowment) and the socioeconomic characteristics of the population that lives nearby. Through spatial analysis, five areas of the city are defined, corresponding to each category of a socioeconomic index (SEI), where the existing PGS within each of them are examined. The results show a substantial difference in favor of the areas inhabited by people with higher socioeconomic privileges; this tendency is clear, since, as the socioeconomic scale moves to a lower level, the characteristics of the PGS also decrease.